Intra-articular damage and patient outcome comparison between athletes and nonathletes after hip arthroscopy - Shapira, J.; Glein, R. M.; Yelton, M. J.; Maldonado, D. R.; Lall, A. C.; Domb, B. G. (The American Journal of Sports Medicine, 2022)
Background: The body of literature comparing hip arthroscopy between athletes and nonathletes is relatively scarce. Analyzing these groups can help to shed light on the severity of intra-articular damage and end-stage osteoarthritis that may result from participation in strenuous activities.